Pengaruh Current Ratio, Debt To Asset Ratio, dan Gross Profit Margin terhadap Kinerja Keuangan pada Perusahaan Manufaktur Sub Sektor Aneka Industri yang Terdaftar di ISSI - Erwin Christian Tampubolon; Dian Ayu Andriani (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The financial performance of manufacturing companies is crucial for sustaining growth, attracting investors, and ensuring competitive advantage. In the Indonesia Sharia Stock Index, companies in the miscellaneous industry subsector face challenges in balancing profitability, liquidity, and capital structure to achieve optimal performance. This study aims to examine the partial and simultaneous effects of Current Ratio (CR), Debt to Asset Ratio (DAR), and Gross Profit Margin (GPM) on financial performance. The population consists of 41 companies, and purposive sampling resulted in 10 companies observed over four years (2021–2024), yielding 36 valid observations after removing outliers. Multiple linear regression analysis was used to evaluate the relationships among the variables. The findings reveal that Gross Profit Margin has a strong and positive effect on financial performance, emphasizing the importance of efficient cost management and revenue generation. In contrast, Current Ratio and Debt to Asset Ratio show limited or negative effects when analyzed individually, but together they significantly influence overall financial outcomes. These results suggest that companies should adopt a holistic approach to managing profitability, liquidity, and capital structure. By focusing on maximizing profit efficiency while maintaining balanced liquidity and prudent debt management, companies can enhance sustainable financial performance in a competitive market environment.